Pemberdayaan Masyarakat Melalui Pelatihan Kerajinan Tali dan Anyaman dari Pelepah Pisang di Desa Mulyorejo Bojonegoro - Dwi Cahyani, Olivia (Badan Usaha Milik Desa Berkaho Pungpungan, 2025)
This community service activity aims to empower the residents of Mulyorejo Village, Tambakrejo District, Bojonegoro Regency, through training in rope-making and weaving crafts using banana trunk fiber. Banana trunk was chosen as the primary material due to its abundance and potential to be transformed into economically valuable products. The implementation method includes preparation, training, and evaluation phases. The results of the activity show that participants improved their understanding and skills in basic rope and weaving techniques and began creating independent product designs. This program not only successfully transferred practical skills but also fostered entrepreneurial interest based on untapped natural materials. With further assistance, the outcomes of this training have the potential to grow into a sustainable community-based enterprise.